If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 6x = -35 Combine like terms: x + 6x = 7x 7x = -35 Solving 7x = -35 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '7'. x = -5 Simplifying x = -5
| x^3-5x^2-66x=0 | | 5-2-7y+8y-3x-10x= | | 40+14s+s^2=0 | | -(4-5y)= | | 2x^2=-5x+12 | | 7x+12=2(x+9) | | 2a-18=-16 | | 3x(x+9)= | | 30x+5000=6350 | | 6(x+20)= | | 7y^2-21y=0 | | x/2=3 | | 30x+500=6350 | | 5n^2-30n=0 | | 3u^2+4u+3=0 | | -9=1+15V+5 | | 50+3=80 | | 103-82=32y-39y | | 9=1+15V+5 | | .33b-8=.5b-4 | | 49x^2=4 | | h=10-4.9t^2 | | 5(4x-5)+25= | | X+15-27+5=176 | | X^2+9=22 | | -14b-20-3=5 | | 9(u+9)=-8u-38 | | 3x+8=5x+2 | | 9x^2+17x+16=8 | | -360=-10(-6b) | | -10(x+5)=100 | | 4w+17=-9(w+1) |